Effect of Intraoperation Dosed Cryoeffect on Functional Activity of Thyroid Gland and Immunological Indices in Patients with Nodular Thyroid Pathology - Karachentsev, Yu. I.; Khaziev, V. V.; Dubovik, V. M.; Lyakh, I. I.; Makedonska, V. O.; Gerasimenko, L. V. (Problems of Cryobiology and Cryomedicine, 2008)
In patients with single nodular non-toxic goiter there was studied the content of thyroid hormones, anti-thyroid antibodies, thyroglobulin prior to organ preserving surgical invasion and in 3 and 6 months after operation with using intraoperation dosed cryoeffect. It has been revealed that no clinical and hormonal signs of post-operative hypothyreosis in any patient was found. In both research groups there was revealed statistically significant, progressing rise of average indices of antibodies to thyroperoxidase and during the whole term of research. In the group of patients after standard surgery such a strengthening of autoimmune process proceeded more intensively if compared with the applied cryoeffect (p <0.001). Use of intraoperation dosed cryoeffect inhibits the activation of antithyroid immunity after surgical invasion, that may affect the development of post-operative thyreosis.